STRENGTHENING STEM LEARNING AT SD KANISIUS BEJI THROUGH ROBOT TRAINING AS AN INNOVATIVE EDUCATIONAL MEDIA - Siswoyo, Agus (Universitas Airlangga, 2025)
This project aims to bring STEM education to life at SD Kanisius Beji by integrating robotics as an engaging and interactive learning tool. Recognizing the importance of STEM in preparing students for the future, the program focuses on hands-on experiences in robotics, programming, and engineering—empowering both teachers and students with practical skills. Through structured workshops and immersive activities, participants explored fundamental robotics concepts in a fun and accessible way, making STEM subjects more approachable while igniting students’ curiosity about technology. The impact was clear: student involvement in STEM activities increased by 30%, and their understanding of robotics and programming improved by 40%. Teachers also felt the benefits, with 90% gaining more confidence in using technology in their lessons. By adopting a hands-on, project-based approach, robotics not only enhanced classroom learning but also encouraged students to engage deeply with engineering challenges. This initiative highlights the power of community-driven education, showing that even elementary schools can successfully integrate advanced STEM learning with the right support. It serves as a model for modernizing traditional teaching methods, ensuring that young learners develop essential problem-solving and critical-thinking skills for the future.